2022
DOI: 10.1007/s40122-022-00448-z
|View full text |Cite
|
Sign up to set email alerts
|

Intercostal Nerve Cryoanalgesia Versus Thoracic Epidural Analgesia in Lung Transplantation: A Retrospective Single-Center Study

Abstract: Introduction:The optimal pain management strategy after lung transplantation is unknown. This study compared analgesic outcomes of intercostal nerve blockade by cryoanalgesia (Cryo) versus thoracic epidural analgesia (TEA). Methods: Seventy-two patients who underwent bilateral lung transplantation via clamshell incision at our center from 2016 to 2018 were managed with TEA (N = 43) or Cryo (N = 29). We evaluated analgesic-specific complications, opioid use in oral morphine equivalents (OME), and pain scores (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Intercostal nerve block has been abandoned due to the high risk of local anesthetic toxicity, the short duration, and the difficulty of leaving a catheter in place for continuous infusion of local anesthetics. However, cryoablation of the intercostal nerve may be an attractive alternative to thoracic epidural analgesia [ 86 ]. Its prolonged analgesic effect, up to 3 to 9 months postoperatively, must be weighed against the risk of direct nerve injury (neuropathic pain and loss of intercostal muscle strength) [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intercostal nerve block has been abandoned due to the high risk of local anesthetic toxicity, the short duration, and the difficulty of leaving a catheter in place for continuous infusion of local anesthetics. However, cryoablation of the intercostal nerve may be an attractive alternative to thoracic epidural analgesia [ 86 ]. Its prolonged analgesic effect, up to 3 to 9 months postoperatively, must be weighed against the risk of direct nerve injury (neuropathic pain and loss of intercostal muscle strength) [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…The findings indicated that ICN cryoablation was safe and provided equal analgesia compared with TEA. Therefore, they concluded that it might be a preferred option in this complex patient population as it can be used in all clinical scenarios and eliminate the risks and delays associated with TEA 52 …”
Section: Intercostal Nerve Block and Cryoablationmentioning
confidence: 99%
“…A more recent modality to prevent both short and long-term post thoracotomy pain, cryoanalgesia has been gaining traction in the transplant community. Cryoanalgesia involves mechanical freezing and killing of intercostal axons while leaving the nerve sheath intact [107]. This allows for several months of significant pain control as the nerve fibers slowly regenerate within the undamaged nerve sheath [107].…”
Section: Pain Controlmentioning
confidence: 99%
“…Cryoanalgesia involves mechanical freezing and killing of intercostal axons while leaving the nerve sheath intact [107]. This allows for several months of significant pain control as the nerve fibers slowly regenerate within the undamaged nerve sheath [107]. Data around cryoanalgesia has been mainly limited to a few studies in posterolateral thoracotomy [108,109].…”
Section: Pain Controlmentioning
confidence: 99%
See 1 more Smart Citation